Pengaruh Fraud Triangle Theory Dalam Mendeteksi Financial Fraud (Studi Kasus Pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2019-2022) - Alfaridzi, Helpan; Diah PA, Enggar; Wijaya Z, Rico (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This research aims to test and analyze the detection of financial fraud using a model developed based on fraud triangle theory in food and beverage companies listed on the Indonesia Stock Exchange in 2019-2022. This type of research is quantitative research with the documentation method. The research population includes 95 companies. The sample selection technique was carried out using purposive sampling method which resulted in 52 companies with a total of 208 samples that met the criteria. The data used is secondary data from the company's annual report and the data collection method is documentation. Data analysis uses the Structural Equation Modeling Partial Least Square (SEM-PLS) approach through SmartPLS 4.0 software. The results revealed that the opportunity and rationalization variables have a significant influence on detecting financial fraud. Meanwhile, the pressure variable does not show a significant effect in detecting financial fraud.